Efficient Access to 2,7-Diarylated Pyrido[3,2-d]pyrimidines Involving Regioselective Pallado-dehalogenation and Suzuki Cross-Coupling Reactions - Tikad, Abdellatif; Dehbi, Oussama; Akssira, Mohamed; Aadil, Mina; Massip, Stéphane; Leger, Jean-Michel; Jarry, Christian; Guillaumet, Gérald; Routier, Sylvain (Synthesis, 2013)
An efficient and original synthesis of various 2,7-disubstituted pyrido[3,2-d]pyrimidines is reported. The first synthesis of 2,7-dichloropyrido[3,2-d]pyrimidine, by selective palladium-catalyzed dechlorination of 2,4,7-trichloropyrido[3,2-d]pyrimidine at C-4, is described and its chemical reactivity is examined. Diarylated pyrido[3,2-d]pyrimidines were synthesized starting from 2,7-dichloropyrido[3,2-d]pyrimidine by regioselective Suzuki cross-coupling reaction at C-2 and then at C-7.
Keywords: pyrido[3,2-d]pyrimidines; palladium; Suzuki cross-coupling reaction; dechlorination; selectivity